Desenvolvimento de substrato cerâmico BiNbO4 para antenas de microfita de sistemas de comunicações sem fio - Carneiro Filho, Ranilson (2010)
The main purpose of this work was the development of ceramic dielectric substrates of bismuth niobate (BiNbO4) doped with vanadium pentoxide (V2O5), with high permittivity, used in the construction of microstrip patch antennas with applications in wireless communications systems. The high electrical permittivity of the ceramic substrate provided a reduction of the antenna dimensions. The numerical results obtained in the simulations and the measurements performed with the microstrip patch antennas showed good agreement. These antennas can be used in wireless communication systems in various frequency bands. Results were satisfactory for antennas operating at frequencies in the S band, in the range between 2.5 GHz and 3.0 GHz.